Influence of Isolated Resistance Exercise on Cardiac Remodeling, Myocardial Oxidative Stress, and Metabolism in Infarcted Rats - Rodrigues, Eder Anderson [UNESP]; Lima, Aline Regina Ruiz [UNESP]; Gomes, Mariana Janini; Souza, Lidiane Moreira [UNESP]; Pontes, Thierres Hernani Dias [UNESP]; Pagan, Luana Urbano [UNESP]; Murata, Gilson Masahiro; Damatto, Felipe Cesar [UNESP]; Carvalho Depra, Igor [UNESP]; Rego, Amanda Bergamo Gonçalves Castro [UNESP]; Reyes, David Rafael Abreu [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP]; et al. (MDPI, 2023)
Introduction: Exercise is an important therapeutic strategy for preventing and treating myocardial infarction (MI)-induced cardiac remodeling and heart failure. However, the myocardial effects of resistance exercise on infarcted hearts are not completely established. In this study, we investigated the effects of resistance exercise on structural, functional, and molecular cardiac alterations in infarcted rats. Methods: Three months after MI induction or simulated surgery, Wistar rats were assigned into three groups: Sham (n = 14); MI (n = 9); and exercised MI (MI-Ex, n = 13). Exercised rats performed, 3 times a week for 12 weeks, four climbs on a ladder with progressive loads. Cardiac structure and left ventricle (LV) function were analyzed by echocardiogram. Myocyte diameters were evaluated in hematoxylin- and eosin-stained histological sections as the smallest distance between borders drawn across the nucleus. Myocardial energy metabolism, lipid hydroperoxide, malondialdehyde, protein carbonylation, and antioxidant enzyme activities were evaluated by spectrophotometry. Gene expressions of NADPH oxidase subunits were evaluated by RT-PCR. Statistical analyses were performed using ANOVA and Tukey or Kruskal–Wallis and Dunn’s test. Results: Mortality did not differ between the MI-Ex and MI groups. MI had dilated left atrium and LV, with LV systolic dysfunction. Exercise increased the maximum load-carrying capacity, with no changes in cardiac structure or LV function. Myocyte diameters were lower in MI than in Sham and MI-Ex. Lactate dehydrogenase and creatine kinase activity were lower in MI than in Sham. Citrate synthase and catalase activity were lower in MI and MI-Ex than in Sham. Lipid hydroperoxide concentration was lower in MI-Ex than in MI. Nox2 and p22phox gene expressions were higher in MI-Ex than in Sham. Gene expression of Nox4 was higher in MI and MI-Ex than in Sham, and p47phox was lower in MI than in Sham. Conclusion: Late resistance exercise was safe in infarcted rats. Resistance exercise improved maximum load-carrying capacity, reduced myocardial oxidative stress, and preserved myocardial metabolism, with no changes in cardiac structure or left ventricle function in infarcted rats.
Keywords: metabolism enzymes; myocardial infarction; NADPH oxidase; physical exercise; rat; ventricular function